Form 2 Mathematics – QUADRATIC EQUATION

Share this post on:


QUADRATIC EQUATION

Is any equation which can be written in the form of ax2 + bx + c=0 where a ≠ 0 and a, b and c are real numbers.

SOLVING QUADRATIC EQUATION


i) BY FACTORIZATION

Example 1

solve x2 + 3x – 10 = 0

Solution:

x2 + 3x – 10 = 0

(x2 – 2x) + 5 (x – 2) = 0

x (x – 2) + 5 (x – 2) = 0

(x + 5) (x – 2) = 0

Now x + 5 = 0 or x – 2 = 0

        x = -5 or x = 2

        x = -5 or 2

 
 

Example 2

Solve for x

i) 2x2 + 9x + 10 = 0

Solution:

Sum = 9

Product = 2 x 10 = 20

20 = 1 x 20

      = 2 x 10

      = 4 x 5

(2x2 +4x) + (5x + 10) = 0

2x(x + 2) + 5(x + 2) = 0

(2x + 5) (x + 2) = 0

Now,

2x + 5 = or x + 2 = 0

x= -2.5 or -2

 
 

ii) 2x2 – 12x = 0

Solution:

2x(x – 6) = 0

2x = 0 or x – 6 = 0

X = 0, or x = 6

X = 0 or 6

 
 

iii) x2 – 16 = 0

Solution:

x2 – 16 = 0

(x2) – (4)2 = 0

(x + 4) (x – 4) = 0

Now,  x + 4 = 0 or x – 4 = 0

x = -4 or x = 4

 
 

EXERCISE

1. Solve for x from

X2 – 7x + 12=0

Solution:

x2 – 3x – 4x + 12 = 0

(x2 – 3x) – (4x – 12) = 0

x(x – 3) – 4(x – 3) = 0

(x – 4) (x – 3) = 0

Now,  x – 4 = 0 or x – 3 = 0

x= 4 or x = 3

 
 

ii) 4x2 – 20x + 25 = 0

Solution:

4x2 – 10x – 10x – 25 = 0

(4x2 – 10x) – (10x – 25) = 0

2x(2x – 5) – 5(2x – 5) = 0

(2x – 5) (2x – 5) = 0

Now,    2x – 5 = 0 or 2x – 5 = 0

x = edu.uptymez.com

iii) 4x2 – 1 = 0

Solution:

4x2 – 1 = 0

22x2 – 1 = 0

(2x)2 – (1)2 = 0

(2x + 1) (2x – 1) = 0

Now,    2x + 1 = 0, or 2x – 1 = 0

X = edu.uptymez.com  or x =edu.uptymez.com

iv) (x – 1)2 – 81 = 0

Solution:

(x – 1)2 – 92 = 0

(x – 1 – 9)(x – 1 + 9) = 0

Now, x – 1 – 9 = 0, or x – 1 + 9

          x – 10 = 0, x + 8 = 0

         x = 10  or x = – 8

v) 2x2 = 10x

Solution:

2x2 – 10x = 0

2x(x – 5) = 0

2x = 0 or x – 5 = 0

x = 0, or x = 5

 
 

SOLVING BY COMPLETING THE SQUARE

Example 1

Solve i) 2x2 + 8x – 24 = 0

Solution:

edu.uptymez.com

x2 + 4x – 12 = 0

x2 + 4x = 12

x2 + 2x + 2x + 4 = 12 + 4

(x2 + 2x) + (2x + 4) = 16

x(x+ 2) + 2(x +2) = 16

(x +2) (x +2) = 16

(x +2)2 = 16

       edu.uptymez.com   = edu.uptymez.com

 x + 2 = edu.uptymez.com 4

X = edu.uptymez.com4 edu.uptymez.com2

X = 2 or x =edu.uptymez.com 6

X = 2 or edu.uptymez.com6

 
 

ii) x2 + 5x – 14 = 0

 solution:

x2 + 5x = 14

(x2 + edu.uptymez.com) + (edu.uptymez.com + edu.uptymez.com) = 14 + edu.uptymez.com

x(x + edu.uptymez.com) +edu.uptymez.com (x + edu.uptymez.com) =  edu.uptymez.com

(x + edu.uptymez.com)(x + edu.uptymez.com) = edu.uptymez.com

    edu.uptymez.com =  edu.uptymez.com        

    x + edu.uptymez.com   =  edu.uptymez.com edu.uptymez.com 

   x= edu.uptymez.com edu.uptymez.com edu.uptymez.com or x = edu.uptymez.com edu.uptymez.com edu.uptymez.com edu.uptymez.com                                                                                                                                      

x = 2 or edu.uptymez.com7

iii) 3x2 – 7x– 6 = 0

Solution:

x2edu.uptymez.com – 2 = 0

x2edu.uptymez.com  = 2

x2edu.uptymez.com  – edu.uptymez.com + edu.uptymez.com  = 2 + edu.uptymez.com 

(x2edu.uptymez.com ) –( edu.uptymez.com – edu.uptymez.com )=  edu.uptymez.com

x(x – edu.uptymez.com ) – edu.uptymez.com  (x– edu.uptymez.com )= edu.uptymez.com

         (x– edu.uptymez.com )(x– edu.uptymez.com )= edu.uptymez.com

edu.uptymez.com   = edu.uptymez.com     

      x – edu.uptymez.com  = edu.uptymez.com  edu.uptymez.com

Now,

      x – edu.uptymez.com  =   edu.uptymez.com   ,   x – edu.uptymez.com  = edu.uptymez.com  edu.uptymez.com

x = 3  or x = edu.uptymez.com  edu.uptymez.com

iv) x2 – 5x + 2 = 0

x2 – 5x = -2

x2edu.uptymez.comedu.uptymez.com + edu.uptymez.com = -2 + edu.uptymez.com

x(x – edu.uptymez.com–) – edu.uptymez.com (x – edu.uptymez.com–) = edu.uptymez.com

 (x – edu.uptymez.com)2 = edu.uptymez.com

 
 

edu.uptymez.comedu.uptymez.com

x – edu.uptymez.com  =   ±edu.uptymez.com

x =  edu.uptymez.com  ±edu.uptymez.com

 
 

x = edu.uptymez.comor  edu.uptymez.com                                                                                                                                      
                                                                                                                                         

GENERAL FORMULA

1. Solve ax2 + bx + c = 0

Solution:

edu.uptymez.com 

x2
+ edu.uptymez.com  + edu.uptymez.com   = 0

x2
+ edu.uptymez.com  =edu.uptymez.com edu.uptymez.com  

x2
+ edu.uptymez.com  + edu.uptymez.com   + edu.uptymez.com  = edu.uptymez.com edu.uptymez.com + edu.uptymez.com                                                                                         

(x2
+ edu.uptymez.com ) +( edu.uptymez.com   + edu.uptymez.com ) =  edu.uptymez.com                                  

x(x + edu.uptymez.com ) +   edu.uptymez.com (  x  + edu.uptymez.com ) =  edu.uptymez.com

(x + edu.uptymez.com )2 = edu.uptymez.com

  edu.uptymez.com  =  edu.uptymez.com                                                                                     

        x + edu.uptymez.com  = edu.uptymez.com edu.uptymez.com

                x =edu.uptymez.com edu.uptymez.com  edu.uptymez.com edu.uptymez.com

Generally, edu.uptymez.com

Example 1.

Solve for x by using generally formula

i) 6x2 + 11x + 3 = 0

Solution:  a = 6, b = 11, c = 3

From the general equation, edu.uptymez.com 

                                     edu.uptymez.com       

                                      edu.uptymez.com     

                                       edu.uptymez.com

                                       edu.uptymez.com 

                           edu.uptymez.com    and  edu.uptymez.com

                           edu.uptymez.com   and    edu.uptymez.com

 
 

ii) 5x2 – 6x – 1 = 0

Solution:

a= 5, b = -6, c =1

From the general equation, edu.uptymez.com 

                                      edu.uptymez.com       

                                      edu.uptymez.com     

                                       edu.uptymez.com

                                       edu.uptymez.com 

                               edu.uptymez.com    and  edu.uptymez.com

                               edu.uptymez.com   and    edu.uptymez.com

 
 

 
 

iii) 0 = 400 + 20t – t2

solution:

t2
edu.uptymez.com 20t edu.uptymez.com 400 = 0

a = 1, b = -20, c = -400

From the general equation
                                   edu.uptymez.com

                                     edu.uptymez.com       

                                     edu.uptymez.com     

                                     edu.uptymez.com

                                    edu.uptymez.com

 
 

GRAPHICAL SOLUTION OF QUADRATIC  EQUATION

          The general quadratic equation ax2 + bx + c =0 can be solved graphically

          First draw the graph by setting ax2 + bx + c = y and then

Drawing graphs

Example 1

Draw the graph of the following equation

i) y = x2 – 3

ii) y = 2 – x2

iii) y = x2 + x – 1

Solution:

i) y = x2 – 3

TABLE VALUE

      

x

-3

-2

-1

0

1

2

3

y

6

1

-2

-3

-2

1

6

edu.uptymez.com

                                                             
 

 

edu.uptymez.com


ii) y = 2 – x2      

edu.uptymez.com

                                                                                                        
 

                                                                                                          
        edu.uptymez.com                                                                     

 
 

 
 

         iii) y = x2 + x – 1

Solution:
edu.uptymez.com

 edu.uptymez.com

                           
 

APPLICATION OF GRAPHS IN SOLVING QUADRATIC EQUATION

a) Solve graphically the equation x2 – x – 6 = 0

b) Use the graph in a to solve the equation

x2 – x – 2 = 0


Solution:
x2 – x – 6 = 0

Let y=x2 – x – 6…………………….(i) Then
      y=0………………….(ii)
  
edu.uptymez.com

    edu.uptymez.com

   (b)From x2 – x – 6 = 0                      

     Then
              x2 – x – 2 = 0 can be written as
              x2 – x –2-4 = 0-4
            x2 – x – 6 = -4   But y=x2 – x – 6
     
y=-4

x=-1 or x=2

More examples

1. A man is 4 times as old as his son. In 4 years the product of their ages will be 520.

Find the sons present age

   edu.uptymez.com 

Now

(x + 4) (4x + 4) = 520

4x2 + 4x + 16x + 16 = 520

edu.uptymez.com +  edu.uptymez.com – edu.uptymez.com = edu.uptymez.com

x2 + 5x – 126 = 0

a=1, b = 5, c = -126

From the general equation, edu.uptymez.com 

                                      edu.uptymez.com       

                                      edu.uptymez.com     

                                      edu.uptymez.com

                                      edu.uptymez.com 

                           edu.uptymez.com    and  edu.uptymez.com

                           edu.uptymez.com   and    edu.uptymez.com

 
 

                           x = 9   or   -14.

              The present age of the son is 9

2.Find the consecutive numbers such that the sum of their squares is equal to 145

Solution:

Let x be the first number and x + 1 be the second number

Sum of x2 + (x + 1)2 = 145 their squares

Now, x2 + (x + 1)2 = 145

x2 + x2 + 2x + 1 = 145

2 x2 + 2x  – 144  = 0

Divide by 2 both sides , then x2 + x – 72

 
 

a =1, b =1, c = -72

                           From the general equation, edu.uptymez.com 

                           edu.uptymez.com       

                           edu.uptymez.com     

                           edu.uptymez.com

                           edu.uptymez.com 

                           edu.uptymez.com    and  edu.uptymez.com

                           edu.uptymez.com   and    edu.uptymez.com

 x =  8  and   9                                                                                             

or  x = -9 and -8

The two consecutive numbers are 8 and 9 or -9 and -8.

 
 

Share this post on: